Comparative evaluation of 64-slice CT angiography and digital subtraction angiography in assessing the cervicocranial vasculature - Klingebiel, Randolf (Dove Medical Press, 2008)
BACKGROUND: Noninvasive 64-slice computed tomography angiography (64-MSCTA) closely approximates conventional catheter angiography (DSA) in terms of detail resolution. OBJECTIVE: Retrospective evaluation of cervicocranial (cc) 64-MSCTA in comparison with DSA in patients with presumptive cc vascular disorders. MATERIAL AND METHODS: Twenty-four 64-MSCTA studies (32 mm detector width, slice thickness 0.5 mm, 120 kv, 150 mAs, pitch 0.75) of patients with presumptive cc vascular pathology (13 men, 11 women, mean age 38.3 ± 11.3 yrs, range 19–54 yrs) were assessed in comparison with DSA studies without abnormal findings in age matched patients (11 men, 13 women, mean age 39.7 ± 11.9 yrs, range 18–54 yrs). Study readings were performed in a blinded manner by two neuroradiologists with respect to image quality and assessibility of various cc vascular segments by using a five point scale. Radiation exposure was calculated for 64-MSCTA. RESULTS: Each reader assessed 384/528 different vessel segments (64-MSCTA/DSA). Superior image quality was attributed to DSA with respect to the C1 ICA–C6 ICA, A3 ACA, and P3 PCA segments as well the AICA and SCA. 64-MSCTA was scored superior for C7 ICA and V4 VA segments. A significantly increased number of nonassessable V2- and V3 VA segments in DSA studies was noted. The effective dose for 64-MSCTA amounted to 2.2 mSv. CONCLUSIONS: 64-MSCTA provides near-equivalent diagnostic information of the cc vasculature as compared with DSA. According to our results, DSA should be considered primarily when peripheral vessels (A3/P3) or ICA segments close to the skull base (C2-5) are of interest, such as in primary angiitis or stenoocclusive ICA disease, respectively.